2009
DOI: 10.1002/elps.200800670
|View full text |Cite
|
Sign up to set email alerts
|

Recent food safety and food quality applications of CE‐MS

Abstract: The first on-line coupling of CE with MS detection more than 20 years ago provided a very powerful technique with a wide variety of applications, among which food analysis is of special interest, especially that dealing with food safety and food quality applications, the major topics of public interest nowadays. With this review article, we would like to show the most recent applications of CE-MS in both fields by recompiling and commenting articles published between January 2004 and October 2008. Although bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 127 publications
(147 reference statements)
0
21
0
Order By: Relevance
“…milk, kidney, fruit, wine, tea, fish, juice and chicken, among others). Although there are scientific articles showing the potential of electrophoretic methods using real samples [4,7,[16][17][18][19], unfortunately, it is not always possible to find papers in which the authors have demonstrated the potential of the CE methodologies using samples in which the analytes are in native form and consequently the interaction matrix-analyte is unpredictable. In most cases, spiked samples are used to demonstrate this relative potential.…”
Section: Ce Companies and Market Statusmentioning
confidence: 95%
“…milk, kidney, fruit, wine, tea, fish, juice and chicken, among others). Although there are scientific articles showing the potential of electrophoretic methods using real samples [4,7,[16][17][18][19], unfortunately, it is not always possible to find papers in which the authors have demonstrated the potential of the CE methodologies using samples in which the analytes are in native form and consequently the interaction matrix-analyte is unpredictable. In most cases, spiked samples are used to demonstrate this relative potential.…”
Section: Ce Companies and Market Statusmentioning
confidence: 95%
“…Focusing on interfacing-and coupling-related parameters, several review papers include extensive tables listing separation-and detection-relevant data such as BGE composition and also SL composition and flow rates [22][23][24][25][26][27][28][29][30][31][32]. Browsing through these tables, several findings regarding SL composition can be deducted.…”
Section: Sheath-liquid Compositionmentioning
confidence: 99%
“…Rarely, acetonitrile or ethanol is the basis of an SL, whereas there are several examples for mixtures of methanol or iso-propanol with acetonitrile as SL. A comprehensive picture displaying the variety of mixtures used as SL can be obtained from reviews on CE-MS [22][23][24][25][26][27][28][29][30][31][32].…”
Section: Sheath-liquid Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact CE-MS proteomic methods account for a single paragraph on the tenth page. So although CE-MS can have numerous applications in food safety and food quality [28] its use in proteomics is limited and therefore its routine use as highthroughput proteomics in food and seafood is just in its infancy. One of the issues arising from this topic is an exact definition of what a high-throughput application actually is.…”
Section: High-throughput Mass Spectrometry Applications For Quality Cmentioning
confidence: 99%